Late onset toxicities associated with the use of CDK 4/6 inhibitors in hormone receptor positive (HR+), human epidermal growth factor receptor-2 negative (HER2-) metastatic breast cancer patients: a multidisciplinary, pan-EU position paper regarding their optimal management. The GIOCONDA project - Cazzaniga, Marina Elena; Ciaccio, Antonio; Danesi, Romano; Duhoux, Francois P.; Girmenia, Corrado; Zaman, Kalhil; Lindman, Henrik; Luppi, Fabrizio; Mavroudis, Dimitrios; Paris, Ida; Olubukola, Ayodele; Samreen, Ahmed; et al. (Frontiers in Oncology, 2023)
The personalization of therapies in breast cancer has favoured the introduction of new moleculartargeted therapies into clinical practice. Among them, cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitors have acquired increasing importance, with the approval in recent years of palbociclib, ribociclib, and abemaciclib in combination with endocrine therapy. Currently, no guidelines are available to monitor and manage potential long-term toxicities associated with the use of these drugs. A multidisciplinary panel of European oncologists, was supported by a pharmacologist, a hematologist, a hepatologist and a pulmonologist to discuss the management of long-term toxicities, based on the literature review and their clinical experience The panel provided detailed roadmaps to manage long-term toxicities associated with the use of CDK4/6 inhibitors in clinical practice.Knowing the frequency and characteristics of the toxicity profile associated with each CDK4/6 inhibitor is important in the decision-making process to match the right drug to the right patient.